Production of pyruvic acid from glycerol by Yarrowia lipolytica - Cybulski, Krzysztof; Tomaszewska-Hetman, Ludwika; Rakicka, Magdalena; Juszczyk, Piotr; Rywińska, Anita (Folia microbiologica, 2019)
The aim of the study was to screen Yarrowia lipolytica strains for keto acid production and determine optimal conditions for pyruvic acid biosynthesis from glycerol by the best producer. The analyzed parameters were thiamine concentration, medium pH, stirring speed, and substrate concentration. The screening was performed in flask cultures, whereas pyruvic acid production was carried out in 5-L stirred-tank reactor with 2 L of working volume. In total, 24 Y. lipolytica strains were compared for their abilities to produce pyruvic and α-ketoglutaric acids. The total concentration of both acids ranged from 0.1 to 15.03 g/L. Ten strains were selected for keto acid biosynthesis in bioreactor. The Y. lipolytica SKO 6 strain was identified as the best producer of pyruvic acid. In the selected conditions (thiamine concentration 1.5 μg/L, pH 4.0, stirring speed 800 rpm, 150 g/L of glycerol), the strain Y. lipolytica SKO 6 produced 99.3 g/L of pyruvic acid, with process yield of 0.63 g/g and volumetric production rate of 1.18 g/L/h. Higher titer of pyruvic acid was obtained during fed-batch culture with 200 g/L of glycerol, reaching 125.8 g/L from pure glycerol (yield 0.68 g/g) and 124.4 g/L from crude glycerol (yield 0.62 g/g). Results obtained for the strain Y. lipolytica SKO 6 proved the suitability of microbial production of pyruvic acid at industrial scale.
Keywords: Culture Media; techniky vsádkové kultivace; glycerol; kyselina pyrohroznová; thiamin; Pyruvic Acid; Glycerol; bioreaktory; kyseliny ketoglutarové; Bioreactors; Yarrowia; Batch Cell Culture Techniques; Ketoglutaric Acids; Thiamine; kultivační média